Overnight company II a plant design on the manufacture of fatty alcohols from coconut oil - Aquino, Virgilio A.; Nunez, Caesar T.; Soriano, Maria Luisa R. (Quezon City College of Engineering, 1977)
Plant site: Atimonan, Quezon -- Capacity: 50 tons feed coconut oil a day -- Fixed capital costs: P 31,980,000.00 -- Working capital: P 5,436,600.00 -- Total capital investment: P 37,416,600.00 -- Break-even point: 51% -- Payout time: before taxes 2.92 years, after taxes 3.89 years
Typescript.
Plant design.
Keywords: Factories -- Design and construction; Fatty alcohols; Coconut